Revolutionizing Diabetes and Obesity Management: A Comprehensive Review of Tirzepatide's Dual Agonist Approach - Sonam Samal; Sourav Maiti; Jonnalagadda Vihari (Dr. Annil Mahajan, 2024)
Tirzepatide, an innovative glucagon-like peptide-1 (GLP-1) and glucagon receptor dual agonist, has emerged as a promising therapeutic avenue for type 2 diabetes and obesity management. This review encompasses a comprehensive evaluation of Tirzepatide's mechanism of action, clinical efficacy, safety profile, and comparative effectiveness against existing treatments. By targeting multiple pathways related to glucose and weight regulation, Tirzepatide exhibits superior glycemic control and substantial weight loss, presenting a novel approach to address the intertwined challenges of diabetes and obesity. An analysis of pivotal clinical trials, potential adverse effects, and future directions in Tirzepatide research further underscores its potential as a transformative treatment strategy.